Bee hotels to boost bees after bushfires Report - Prendergast, Kit; Wilson, Rachele (Curtin University, 2022)
The project Bee hotels to boost bees after bushfires supported the recovery of native bee populations by installing artificial nesting substrates (bee hotels) in areas of high biodiversity value that were impacted by the 2019/20 bushfires. This was achieved through an Australia-wide citizen science effort, as well as through intensive monitoring of 100 bee hotels (50 bamboo and 50 wooden) and visual surveys at five burnt sites and three control sites by a native bee ecologist. We recruited and provided information resources to 63 community groups and citizens to support native bee recovery in fire-affected regions across the country. An iNaturalist project facilitated citizen science data collection and allowed us to evaluate the impact of installed bee hotels and their uptake by bees. 195 observations were uploaded to this project by citizen scientists. Importantly, at least 900 nests were created by bees in the bee hotels installed for this project and significantly more bees were observed in sites with bee hotels compared to control sites (nearby burnt sites without bee hotels). All milestones were met within the anticipated timeline (Table 1) and budget, even with setbacks for some participants due to the pandemic. The project also attracted many participants and nation-wide interest, thus increasing awareness of native cavity nesting bees.